AWARENESS, ATTITUDES, PREVENTION, AND PERCEPTIONS OF COVID-19 OUTBREAK AMONG NURSES IN SAUDI ARABIA - Al-Dossary, Reem; Alamri, Majed; Albaqawi, Hamdan; Al Hosis, Khaled; Aljeldah, Mohammed; Aljohan, Mohammed; Aljohani, Khalid; Almadani, Noura; Alrasheadi, Bader; Falatah, Rawaih; Almazan, Joseph (MDPI, 2020)
he newly discovered coronavirus (COVID-19) has become a pandemic, infecting thousands of people around the world. This study examines nurses’ demographic information (age, gender, marital status, area of practice, total years of experience in the current hospital, work region, monthly salary, educational level, workplace, nationality, working hours per day, total nursing experience, and the respondents’ main source of information on COVID-19), awareness, attitudes, prevention, and perceptions of COVID-19 during the outbreak in Saudi Arabia. A cross-sectional descriptive design of 500 nurses working at government and non-governmental hospitals in five regions in Saudi Arabia were selected using convenience sampling. The Kruskal–Wallis test was applied and the Mann–Whitney test was utilized as a post hoc test. The majority of nurses in this study, 96.85%, had excellent knowledge of COVID-19. Some (83.2%) of nurses reported significant prevention knowledge and treatment skills about COVID-19, while 7.6% had little knowledge about prevention. More than half of the nurses (60.4%) had high positive attitudes toward caring for COVID-19 patients. In conclusion, female nurses, married nurses, and bachelor’s degree nurses had greater awareness, better attitude, and prevention clinical experience towards COVID-19. Meanwhile, non-Saudi nurses had higher self-reported awareness, positive attitudes, optimal prevention, and positive perceptions compared to Saudi nurses. This study provides baseline information immediately needed to enable health authorities to prioritize training programs that support nurses during the COVID-19 pandemic. Keywords: COVID-19; nurses; outbreak; pandemic; Saudi Arabia
Keywords: COVID-19; nurses; outbreak; pandemic; Saudi Arabia; Research Subject Categories::MEDICINE